Pubertal attainment and Leydig cell function following pediatric hematopoietic stem cell transplantation: a three-decade longitudinal assessment - Cattoni, Alessandro; Nicolosi, Maria Laura; Capitoli, Giulia; Gadda, Alberto; Molinari, Silvia; Louka, Sotiris; Buonsante, Andrea; Orlandi, Simona; Salierno, Gianluca; Bellani, Iacopo; Vendemini, Francesca; Ottaviano, Giorgio; et al. (Frontiers in Endocrinology, 2023)
Introduction. Impaired testosterone secretion is a frequent sequela following haematopoietic stem cell transplantation (HSCT) in pediatrics, but long-term longitudinal trendlines of clinical and biochemical findings are still scanty.Methods. Monocentric, retrospective analysis. Male patients transplanted <18 years between 1992 and 2021, surviving ≥2 years after HSCT and showing, upon enrollment, clinical and biochemical signs consistent with pubertal onset and progression were included. Clinical and biochemical data collected every 6-12 months were recorded.Results. Of 130 patients enrolled, 56% were prepubertal, while 44% were peri-/postpubertal upon HSCT. Overall, 44% showed spontaneous progression into puberty and normal gonadal profile, while the remaining experienced pubertal arrest (1%), isolated increase of FSH (19%), compensated (23%) or overt (13%) hypergonadotropic hypogonadism. Post-pubertal testicular volume (TV) was statistically smaller among patients still pre-pubertal upon HSCT (p 0.049), whereas no differences were recorded in adult testosterone levels. LH and testosterone levels showed a specular trend between 20 and 30 years, as a progressive decrease in sexual steroids was associated with a compensatory increase of the luteinizing hormone.A variable degree of gonadal dysfunction was reported in 85%, 51%, 32% and 0% of patients following total body irradiation-(TBI), busulfan-, cyclophosphamide-and treosulfan-based regimens, respectively.TBI and busulfan cohorts were associated with the lowest probability of gonadal event-free course (p<0.0001), while it achieved 100% following treosulfan. A statistically greater gonadotoxicity was detected after busulfan than treosulfan (p 0.024). Chemo-only regimens were associated with statistically larger TV (p <0.001), higher testosterone (p 0.008) and lower gonadotropin levels (p <0.001) than TBI. Accordingly, the latter was associated with a 2-fold increase in the risk of gonadal failure compared to busulfan (OR 2.34, whereas being pre-pubertal upon HSCT was associated with a reduced risk (OR 0.15, CI 0.08-0.30).Conclusions a) patients pre-pubertal upon HSCT showed a reduced risk of testicular endocrine dysfunction, despite smaller adult TV; b) patients showed downwards trend in testosterone levels after full pubertal attainment, despite a compensatory increase in LH; c) treosulfan was associated to a statistically lower occurrence of hypogonadism than busulfan, with a trend towards larger TV, higher testosterone levels and lower gonadotropins.